2020
DOI: 10.2174/1871530320666200515112853
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: The New Global Epidemic Pharmacological Treatment, Opportunities and Limits for Personalized Therapy

Abstract: Background: The increase in global obesity rates over the past three decades has been remarkable, a true epidemic, both in developed and in developing countries. The projections, based on current trends, suggest an increase in the prevalence of obesity at 60% in adult men, 40% in adult women and 25% in children in 2050. Given the limitations of lifestyle and surgery interventions bariatric, drug therapy approaches for the treatment of obesity, therefore become important options. Aim: The purpose of this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 76 publications
1
12
0
1
Order By: Relevance
“…The Report on Nutrition and Chronic Disease Status of Chinese Residents (2020) showed that the overweight and obesity rate of Chinese adult residents exceeded 50%. Based on current trends, the projections suggested an increase in the prevalence of obesity to 40% in adult women, 60% in adult men, and 25% in children by the year 2050 (Milano et al, 2020 ). Obesity is often accompanied by other metabolic diseases, such as hyperlipidemia, hypercholesterolemia, cardiovascular disease, liver steatosis, and type 2 diabetes mellitus (T2DM), all of which increase the risk of death (Mayoral et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Report on Nutrition and Chronic Disease Status of Chinese Residents (2020) showed that the overweight and obesity rate of Chinese adult residents exceeded 50%. Based on current trends, the projections suggested an increase in the prevalence of obesity to 40% in adult women, 60% in adult men, and 25% in children by the year 2050 (Milano et al, 2020 ). Obesity is often accompanied by other metabolic diseases, such as hyperlipidemia, hypercholesterolemia, cardiovascular disease, liver steatosis, and type 2 diabetes mellitus (T2DM), all of which increase the risk of death (Mayoral et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An enrichment of immune factors and cells in adipose is associated with obesity, but their role in the development of obesity and the subsequent metabolic sequelae remains less understood (Bischoff et al, 2016;Cohen et al, 2011;Milano et al, 2020;Reilly and Saltiel, 2017;Van Pelt et al, 2017). Since the identification of secreted cytokine mediators of inflammation (e.g., TNFa, IL-1b, and IL-6), there has been an effort to connect signaling between these cytokines and the different cells within adipose tissue including adipocytes and stromal, vascular, and immune cells (Ferrante, 2013;Han et al, 2020;Kosteli et al, 2010;Lumeng et al, 2007aLumeng et al, , 2007bLumeng et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…3 People who are considered as obese (ie, have a body mass index of over 30, based upon their weight and height) are at significantly higher risk for many noncommunicable diseases, including cardiovascular diseases, diabetes, musculoskeletal disorders (mainly osteoarthritis), and several cancers. [1][2][3][4] Obesity is a major risk factor for periodontal disease progression, and the precise mechanisms by which obesity-related factors directly influence periodontal disease pathophysiology have not yet been identified. This creates new challenges and therapeutic opportunities in this era of precision medicine, especially in special populations in which many groups present with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in dietary and physical activity patterns are often a consequence of environmental and societal changes that can affect specific populations 3 . People who are considered as obese (ie, have a body mass index of over 30, based upon their weight and height) are at significantly higher risk for many noncommunicable diseases, including cardiovascular diseases, diabetes, musculoskeletal disorders (mainly osteoarthritis), and several cancers 1‐4 …”
Section: Introductionmentioning
confidence: 99%